Pengembangan Media Pembelajaran Berbasis Android untuk Meningkatkan Pemahaman Matematis Siswa dalam Penerapan Model Problem Based Learning - Natasya Isabel Br. Siahaan; Tiur Malasari Siregar (Lembaga Pengembangan Kinerja Dosen, 2024)
Based on the results of the needs analysis in the learning process, a development of learning media is needed. This research aims to create this product to be more valid, practical and effective in improving students' mathematical understanding. This research and development uses the ADDIE (Analyze, Design, Development, Implementation, and Evaluate) development model. The subjects of this research were 30 students of class X Science 1 at SMA Methodist 7 Medan. The research results show that the Android-based learning media developed has obtained a very high level of validity, with an average percentage of 90.38% according to material experts, 87.77% according to media experts, then 90.90% according to lesson plan validators and results. Validation from experts on pre-test and post-test questions showed a percentage of 92.70% and 91.67%, respectively included in the